EXPLANATIONS OF CLUSTER APPROACH IN EDUCATIONAL CONTEXTS - Normatova Ezoza Habibullo qizi (ZAMONAVIY TA’LIMDA FAN VA INNOVATSION TADQIQOTLAR, 2025)
This article aims to explore the theoretical foundations, practical applications, and pedagogical benefits of the cluster approach in educational contexts. It will highlight how this strategy enhances not only vocabulary development but also overall conceptual learning, making it a valuable tool for educators in a variety of instructional environments.